PERILAKU KORUPSI: ANTARA KEBIASAAN ATAU HASIL PENDIDIKAN (Sebuah Tinjauan Psikologi) - widya laksana, budiarda (AflahConsilia : Jurnal Bimbingan dan Konseling, 2025)
Corrupt behavior is a complex phenomenon that is not only influenced by legal and economic structures, but also by internal individual factors, external influences, and cultural constructions that develop in society. This article aims to analyze from the point of view of psychology whether corruption behavior is more the result of habits formed in the social environment, or the result of an ineffective educational process in building character and integrity. Using a descriptive-qualitative approach, this research examines various relevant literature and empirical studies. The results of the study show that low achievement motivation, (internal factors), environmental pressure and open opportunities (external factors), and culture, namely family culture, culture fatherism and a culture that lacks assertiveness, synergistically form corruption behavior as a habit that is difficult to change. Education that only focuses on cognitive aspects without strengthening moral values also exacerbates this condition. Therefore, corruption prevention requires a multidimensional approach that includes character education, strengthening healthy achievement motivation, and transforming parenting changes that can bring up children's achievement motivation.